Palmer Amaranth (Amaranthus palmeri) Management in GlyTol® LibertyLink® Cotton. (December 2014) - Reed, Jacob D.; Keeling, J. Wayne; Dotray, Peter A.
Abstract : Field trials were conducted in Lubbock, TX in 2010 and 2011 to evaluate tank-mix combinations of glyphosate and glufosinate in GlyTol ® LibertyLink ® cotton for control of Palmer amaranth. Herbicide treatments included glyphosate and glufosinate applied at various tank-mix rate combinations (1X:1X, 1X:0.75X, 1X:0.5X, 1X:0.25X and 1X:0X of glyphosate plus glufosinate), proportional tank-mix rate combinations (1X:0X, 0.75X:0.25X, 0.5X:0.5X, 0.25X:0.75X, and 0X:1X of glyphosate plus glufosinate, where X is 0.84 kg ae ha −1 of glyphosate or 0.58 kg ai ha −1 of glufosinate ammonium), and in sequential (1X followed by 1X) applications of both herbicides in an overall weed management system. Greenhouse studies were conducted to quantify antagonistic or synergistic effects. Treatments included a nontreated control; glyphosate at 0.84, 0.63, 0.42, and 0.21 kg ha −1 ; glufosinate at 0.58, 0.44, 0.29, and 0.15 kg ha −1 ; and all tank-mix combinations of each herbicide rate. Dry weights were converted to percent growth values for each rate of the two herbicides alone, and these values were used to calculate expected responses of tank-mix combinations with the use of Colby's method. Expected values were compared to observed percent growth values using an augmented mixed-model method. Results of field studies indicated that tank mixes of glyphosate and glufosinate were less effective at controlling Palmer amaranth than glyphosate applied alone. The addition of any rate of glufosinate to a 1X rate of glyphosate reduced Palmer amaranth control compared to glyphosate alone. Greenhouse studies confirmed antagonism seen in the field. These results indicate that sequential applications of these two herbicides are a better option for Palmer amaranth weed management.